0
$\begingroup$

How can I prove that for $a,b,c \in ℕ^*$, if $a$|$c$ and $b$|$c$, then $\frac {ab}{(a,b)}$|$c$?

This is what I've tried:

$a$|$c$ and $b$|$c$ implies that $ba$|$bc$ and $ab$|$ac$, so $ab$|$bcx + acy$ and $ab$|$c(bx+ay)$. We know that for some $x$ and $y$, $bx+ay$$=(a,b)$, so $\frac {ab}{(a,b)}$|$c$. Is this right?

Thanks.

$\endgroup$
1
$\begingroup$

Yes, $\ a,b\mid c\,\Rightarrow\, ab\mid ac,bc\,\Rightarrow\, ab\mid(ac,bc)=(a,b)c\,\Rightarrow\,ab/(a,b)\mid c,\ $ where, for variety, I have replaced your use of the Bezout Identity by the GCD Distributive Law.

Remark $\ $ The reverse implications are also true, which shows $\,{\rm lcm}(a,b) = ab/\gcd(a,b).$

$\endgroup$
-1
$\begingroup$

Write a = k(a,b), and b = s(a,b) where (k,s) = 1. So a divides c ==> c = ma =mk(a,b),

and b divides c ==> c = nb = ns(a,b) ==> c/(a,b) = mk = ns. This means k divides c/(a,b), and

s also divides c/(a,b). Since (k,s) = 1, ks divides c/(a,b) . This means:

[a/(a,b)]*[b/(a,b)] divides c/(a,b) , and cancel out (a,b) we get the answer.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.